Flying between raindrops: Strong seasonal turnover of several Lepidoptera groups in lowland rainforests of Mount Cameroon. Issue 24 (3rd December 2018) - Maicher, Vincent; Sáfián, Szabolcs; Murkwe, Mercy; Przybyłowicz, Łukasz; Janeček, Štěpán; Fokam, Eric B.; Pyrcz, Tomasz; Tropek, Robert
Abstract: Although seasonality in the tropics is often less pronounced than in temperate areas, tropical ecosystems show seasonal dynamics as well. Nevertheless, individual tropical insects' phenological patterns are still poorly understood, especially in the Afrotropics. To fill this gap, we investigated biodiversity patterns of Lepidoptera communities at three rainforest localities in the foothills of Mount Cameroon, West Africa, one of the wettest places in the world. Our multitaxa approach covered six lepidopteran groups (fruit‐feeding butterflies and moths, the families Sphingidae, Saturniidae, and Eupterotidae, and the subfamily Arctiinae of Erebidae) with diverse life strategies. We sampled adults of the focal groups in three distinct seasons. Our sampling included standardized bait trapping (80 traps exposed for 10 days per locality and season) and attraction by light (six full nights per locality and season). Altogether, our dataset comprised 20, 576 specimens belonging to 559 (morpho)species of the focal groups. The biodiversity of Lepidoptera generally increased in the high‐dry season, and either increased (fruit‐feeding moths, Arctiinae, Saturniidae) or decreased (butterflies, Sphingidae) in the transition to the wet season in particular groups. Simultaneously, we revealed a strong species turnover of fruit‐feeding Lepidoptera and Arctiinae among the seasons, indicating relatively high specialization of these communities for particular seasons. Such temporal specialization can make the local communities of butterflies and moths especially sensitive to the expected seasonal perturbations caused by the global change. Because of the key role of Lepidoptera across trophic levels, such changes in their communities could strengthen this impact on entire tropical ecosystems. Abstract : Seasonality patterns of several groups of Lepidoptera were investigated at the foothills of Mount Cameroon, West Africa, one of the wettest places worldwide. We revealed a strong species turnover of fruit‐feeding Lepidoptera and Arctiinae among the seasons, indicating the existence of relatively high specialization of these communities for particular seasons.